Modal analysis of multi-disk rotor system - Pradhan, Sunil; Luintel, Mahesh Chandra (Journal of Innovations in Engineering Education, 2024)
Controlling vibrations is essential for the safe and efficient operation of these applications, given the significance of the system’s dynamic behavior. Analyzing the modal of rotor systems with multiple disks and imbalanced masses is a vital field of study within mechanical engineering. Previous research has employed diverse methods, such as experimental testing, analytical modelling, and finite element analysis (FEA), to investigate the dynamic and modal characteristics of rotor systems containing multiple disks and uneven masses. Under the present study, the analytical and mathematical modelling, along with ANSYS platform-based simulations, is the approach for analyzing the dynamic performance of a rotor system with multiple disks. The results were obtained using Modal analysis in ANSYS, this study investigated the natural frequency of the systems corresponding to backward whirl and forward whirl under free response and comparison with mathematical modelling results. The development of mathematical models for the flexural vibrations of a multi-disk assembly involves treating the disks as rigidly connected to a flexible shaft. Equations of motion for these vibrations analysis, the critical frequencies of the system are determined and found to be remarkably similar when compared.